2020
DOI: 10.1111/sum.12658
|View full text |Cite
|
Sign up to set email alerts
|

Effect of farm management on topsoil organic carbon and aggregate stability in water: A case study from Southwest England, UK

Abstract: There are few reliable data sets to inspire confidence in policymakers that soil organic carbon (SOC) can be measured on farms. We worked with farmers in the Tamar Valley region of southwest England to select sampling sites under similar conditions (soil type, aspect and slope) and management types. Topsoils (2–15 cm) were sampled in autumn 2015, and percentage soil organic matter (%SOM) was determined by loss on ignition and used to calculate %SOC. We also used the stability of macroaggregates in cold water (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Furthermore, no effects of such a strict limit on soil properties and crop yields have been quantitatively proven (Loveland & Webb, 2003). More recently, SOC/clay ratios as a proxy for soil structural quality and corresponding optimal SOC/clay levels have been proposed to help farmers evaluate the effect of soil management (Collier et al., 2020; Johannes et al., 2017; Prout et al., 2021). Upper limits or optimum target values have been proposed as the maximum capacity of a given soil to store C (Lawrence‐Smith et al., 2018; H. J. Vogel et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, no effects of such a strict limit on soil properties and crop yields have been quantitatively proven (Loveland & Webb, 2003). More recently, SOC/clay ratios as a proxy for soil structural quality and corresponding optimal SOC/clay levels have been proposed to help farmers evaluate the effect of soil management (Collier et al., 2020; Johannes et al., 2017; Prout et al., 2021). Upper limits or optimum target values have been proposed as the maximum capacity of a given soil to store C (Lawrence‐Smith et al., 2018; H. J. Vogel et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the much greater C:N ratio of the root material of AberMagic and Prior compared to Pasture might render root‐derived SOC to be more stable to microbial decomposition under the grass cultivars because of a stoichiometric requirement for N to support the metabolism of C by the microbial biomass (Sinsabaugh et al, 2013). Increased root biomass and the associated C that it delivers to the soil may bring additional improvements in soil physical quality, such as soil aggregate stability in water (Collier et al, 2021) and hydraulic functioning (Macleod et al, 2013), because of the effect of available C on soil biological organisms that mediate soil self‐organisation (Crawford et al, 2012). Observed differences in soil pH under the two cultivars compared to Pasture may reflect subtle pedological differences down the soil profile rather than different rooting characteristics, but more investigation would be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The sequestration of atmospheric CO 2 through plants into the soil to form soil organic carbon (SOC) is another important ecosystem service contributing to the regulation of climate. Permanent grasslands, with their perennial vegetation and infrequent cultivation, typically have greater SOC stocks than soil under arable land use, particularly in temperate regions (Chapman et al, 2013; Collier et al, 2021; Gregory et al, 2014, 2016; Wiesmeier et al, 2012), though there is recent debate on whether intensively managed grassland is a C sink or source (Chang et al, 2021). There exists, therefore, a great potential to achieve a “win–win” with managed grasslands because they produce food and fibre primarily and increase SOC sequestration secondly, thus offering a potential strategy for climate‐smart agriculture in grassland‐dominated temperate regions in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Correction methods are also needed to provide meaningful intra‐ and inter‐farm comparisons. A recent study in the UK showed the importance of adjusting SOC measurement results by clay contents, because clay minerals can hold structural water that could be mistakenly included as SOC loss during ignition (Collier et al., 2021).…”
Section: Monitoring Strategiesmentioning
confidence: 99%